STRATEGI DAKWAH IPNU-IPPNU DALAM MENGATASI KENAKALAN REMAJA DI KECAMATAN BANYAKAN KEDIRI: - Sri Mulyani (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2022)
The IPNU-IPPNU propaganda strategy in overcoming juvenile delinquency in the Kaligayam hamlet, Banyakan District, Kediri. This research aims to provide information and education. And how are the da'wah strategies in preventing juvenile delinquency such as consuming liquor, dropping out of school and fighting. The negative stigma against juvenile delinquency requires the role and existence of a large organization in a multicultural society. The presence of IPNU-IPPNU is a smart solution that is considered capable of overcoming this problem. In this case, it becomes a long history in the nation's journey for students who contribute from various corners of the country in Indonesia. This study uses a qualitative descriptive model, by providing an overview of the phenomenon with a SWOT analysis approach. Based on the discussion and data results, it can be concluded that the da'wah strategies include Strength (strength), Weakness (weakness). The strategy variants applied by the organization for students are: motivation, holding, competitions, nurturing differences and implementing religious education. The factors that influence include organizational characteristics and environmental characteristics, covering two aspects, namely internal and external.